1997
DOI: 10.1002/crat.2170320614
|View full text |Cite
|
Sign up to set email alerts
|

Some Physicochemical Studies on Organic Analog of Metal‐Nonmetal Eutectics

Abstract: Phase diagram, growth behaviour, thermochemistry and microstructure of organic analog of metalnonmetal systems, namely, urea-succinonitrile system and diphenyl-neopentyl alcohol system, were studied. While phase diagram study shows the formation of simple eutectic in each case, the growth kinetics investigations suggest the applicability of Hillig-Turnbull equation to these systems. The values of entropy of fusion, enthalpy of mixing, Jackson's roughness parameter, interfacial energy and excess thermodynamic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It is found that γ sl0 correspond to the theoretical results γ 4 [64] and the latest experimental data [13,44,45] while are smaller than the early experimental ones [11,40,41]. Moreover, other theoretical results of γ 1 calculated by Rai et al [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64], γ 2 to γ 4 are also listed for comparison purpose. Note that in this case the units of H m and V are taken as J/mol and cm 3 /mol rather than J/g-atom and cm 3 /g-atom listed in Table 2 [69], and H m = nH m and V = nV g Table 2 Comparisons of γ sl0 (T m ) of 38 organic crystals among the model predictions γ sl0 by Eq.…”
Section: γ Sl0 (T M ) Of 38 Organic Crystalsmentioning
confidence: 79%
See 2 more Smart Citations
“…It is found that γ sl0 correspond to the theoretical results γ 4 [64] and the latest experimental data [13,44,45] while are smaller than the early experimental ones [11,40,41]. Moreover, other theoretical results of γ 1 calculated by Rai et al [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64], γ 2 to γ 4 are also listed for comparison purpose. Note that in this case the units of H m and V are taken as J/mol and cm 3 /mol rather than J/g-atom and cm 3 /g-atom listed in Table 2 [69], and H m = nH m and V = nV g Table 2 Comparisons of γ sl0 (T m ) of 38 organic crystals among the model predictions γ sl0 by Eq.…”
Section: γ Sl0 (T M ) Of 38 Organic Crystalsmentioning
confidence: 79%
“…Although γ 1 was claimed to be calculated in terms of Eq. (2.1) with τ lying between 0.30 and 0.35 (τ value was not definitely mentioned) [46][47][48][51][52][53][54][55][56][57][59][60][61][62][63], γ 1 values of fifteen organic crystals are larger than γ 3 , which is determined by Eq. (2.1) with τ = 0.35.…”
Section: γ Sl0 (T M ) Of 38 Organic Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that γ 0 correspond to the theoretical results γ 4 [63] and the latest experimental data [12,43,44] while are smaller than the early experimental ones [10,39,40]. Moreover, other theoretical results γ 1 calculated by Rai et al [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], γ 2 and γ 3 determined in terms of Eq. 2.1 with τ = 0.30 and 0.35, as well as γ 4 in terms of Eq.…”
Section: γ γ γ γ Sl0 (T M ) Of Organic Crystalsmentioning
confidence: 63%
“…Although γ 1 was claimed to be calculated in terms of Eq. 2.1 Synthesis, Characterization and Properties of Nanostructures with τ lying between 0.30 and 0.35 (τ value was not definitely mentioned) [45][46][47][50][51][52][53][54][55][56][58][59][60][61][62], γ 1 values of fifteen organic crystals are larger than γ 3 , which is determined by Eq. 2.1 with τ = 0.35.…”
Section: γ γ γ γ Sl0 (T M ) Of Organic Crystalsmentioning
confidence: 99%